Critical success factors for implementing management by walking around in Dubai's utilities and municipal sector - Hussain Ali, Mohamed Abdalla (2024)
Enhancing employee performance is a key objective in organizational management, and Management by Walking Around (MBWA) has gained popularity as an effective technique, particularly within Dubai's public sector. MBWA involves managers actively engaging with employees through informal, spontaneous interactions as they perform their daily tasks. This approach aims to improve performance by fostering direct, meaningful communication and addressing issues in real-time, thereby creating a more dynamic and responsive work environment. Despite its growing adoption, there are significant gaps in both practical application and conceptual understanding of MBWA. This study addresses these gaps by investigating the Critical Success Factors (CSFs) essential for the effective implementation of MBWA. Utilizing a quantitative research approach with a sample of 480 respondents from Dubai's Utilities and Municipal Sector, the study employs Structural Equation Modeling (SEM) to identify key factors influencing MBWA and its impact on performance. The findings reveal that MBWA significantly enhances performance, with a robust path coefficient of 0.421 and a T-value of 6.134. Among the factors, Communication (CM) stands out with a particularly strong positive effect on MBWA (coefficient of 1.042 and T-value of 10.233), emphasizing the crucial role of effective information exchange. Organizational Culture (CU) also positively impacts MBWA (coefficient of 0.502 and T-value of 9.958), reflecting the importance of shared values and norms. Additionally, Employee Engagement (EE), Enterprise Resource Planning (ERP), Reward Management (RM), Top Management Support (TM), and Training (TR) positively influence MBWA, with coefficients ranging from 0.309 to 0.379. However, Behavior (BE) and Creativity (CT) show negative or insignificant effects, suggesting limited contributions to MBWA. Discovering Facts (DF) and Feedback (FB) also exhibit weak or non-significant effects. Theoretically, this study contributes to trait theory by identifying and categorizing key traits and factors that impact MBWA’s effectiveness. It enriches the theory by linking traits such as Communication, Organizational Culture, and Employee Engagement to successful MBWA implementation, thus providing a comprehensive framework that addresses existing gaps in the literature. Practically, the study offers actionable insights for managers in Dubai’s public sector. By highlighting the CSFs crucial for MBWA's success, it provides clear guidelines for enhancing employee performance through this management technique. The study underscores the importance of fostering a supportive organizational culture and aligning management practices with the identified critical success factors to achieve optimal performance outcomes.